Algebraische Zahlentheorie: 9.8. bis 15.8.1981 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1981)
J. Antoniadis, Köln; M. Fried, Irvine; H.-J. Bartels, Göttingen; A. Fröhlich, London; J. Brinkhuis, London; K. Girstmair, Innsbruck; V. Diekert, Hamburg; G. Gras, Besancon; M. Eichler, Arlesheim; K. Gyóry, Debrecen; G. Frei-Imfeld, Quebec; F. Halter-Koch, Graz; G. Frey, Saarbrücken; F.-P. Heider, Köln; H. Jacobinsky, Göteborg; E. Lamprecht, Saarbrücken; U. Jannsen, Regensburg; M. Laska, Bonn; W. Jehne, Köln; J. B. Leicht, Heidelberg; E. Kani, Heidelberg; H. W. Lenstra Jr., Amsterdam; H. Kisilevsky, Montreal; H. W. Leopoldt, Karlsruhe; N. Klingen, Köln; A. Leutbecher, München; K. Lakkis, Thessalonicki; C. Levesque, Quebec; F. J. van der Linden, Amsterdam; J. Neukirch, Regensburg; F. Lorenz, Münster; H. Opolka, Münster; G. Martens, Erlangen; C. J. Parry, Blacksburg; B. H. Matzat, Karlsruhe; A. Prestel, Konstanz; B. Z. Moroz, Bonn; H. P. Rehm, Karlsruhe; T. Nakahara, Saga; P. Roquette, Heidelberg; M. Neubrand, Bonn; R. Schertz, Köln; B. Schmithals, Dortmund; R. W. van der Waal, Amsterdam; R. J. Schoof, Leiden; C. D. Walter, Dublin; V. Schulze, Berlin; K. Wingberg, Regensburg; H.-D. Steckel, Köln; Noriko Yui, Saarbrücken; H.-J. Stender, Köln; H. Zantema, Amsterdam; G. Tamme, Regensburg; H. G. Zimmer, Saarbrücken; Olga Taussky-Todd, Pasadena
Beitr. teilw. dt., teilw. engl
Keywords: Konferenzschrift